2019
DOI: 10.1002/aenm.201901428
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency Improvement of Near‐Stoichiometric CuInSe2 Solar Cells for Application in Tandem Devices

Abstract: the formation of defect complexes and possibly even phases of ordered defect compounds. [9][10][11][12] Increasing the Cu content toward stoi chiometry can considerably reduce the pre sence of such defects and defect complexes. It has been shown that stoichiometric Cu concentrations can be beneficial for absorber crystallinity, [13] defect density, [7,13] mobility, [14,15] and doping density. [14][15][16] Despite this, solar cells based on Cu stoichiometric CuInSe 2 (CIS) have never reached efficiencies above … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
84
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 82 publications
(89 citation statements)
references
References 39 publications
3
84
1
1
Order By: Relevance
“…RbF). 17 Additionally, due to the implications of composition gradients for the generation of strain and defects, 18 their replacement also emerges as a plausible pathway to enhance the properties of the absorber.…”
Section: Structural Defectsmentioning
confidence: 99%
“…RbF). 17 Additionally, due to the implications of composition gradients for the generation of strain and defects, 18 their replacement also emerges as a plausible pathway to enhance the properties of the absorber.…”
Section: Structural Defectsmentioning
confidence: 99%
“…Thus, to achieve TCOs with higher conductivity and an excellent transmission at the same time, it is desirable to develop TCOs with high carrier mobility instead of high carrier concentration. [ 163,180,195 ] In recent years, hydrogen doped indium oxide (IO:H), [ 83,190 ] zirconium doped indium oxide (IZrO), [ 199,200 ] and indium doped zinc oxide (IZO) [ 177,197 ] electrodes have gained increasing research interest due to their high carrier mobility. Taking advantage of the low free carrier absorption, these TCO electrodes offer superior NIR transparency compared to the FTO electrode.…”
Section: Nir‐transparent Perovskite Solar Cellsmentioning
confidence: 99%
“…[ 163 ] These TCOs are well‐suited for tandem architecture and have already been demonstrated by numerous research works with excellent electrical and optical characteristics. [ 84,197,198,200,211 ] Further research progress on developing high mobility transparent electrode could prove to be extremely beneficial in minimizing the parasitic losses incurred in the TSCs.…”
Section: Pathways For High‐efficiency Tscsmentioning
confidence: 99%
“…As a narrow-bandgap light absorber, a CIS thin film with a Cu content close to stoichiometry was prepared by adding RbF postdeposition treatment, and it was employed in a 4T MHP/CIS tandem solar cell to achieve better efficiency due to the lower recombination of the CIS subcell. [147] Solution processable QDs are advantageous in the design of perovskite-based tandem solar cells because their bandgap is easily tunable based on their size and composition. Manekkathodi et al demonstrated a PCE of 20.2% for 4T MHP/colloidal QD tandem cells using an MoO 3 /Au/Ag/MoO 3 OMO TCE, which improved IR transmittance.…”
Section: (18 Of 24)mentioning
confidence: 99%
“…As a narrow‐bandgap light absorber, a CIS thin film with a Cu content close to stoichiometry was prepared by adding RbF postdeposition treatment, and it was employed in a 4T MHP/CIS tandem solar cell to achieve better efficiency due to the lower recombination of the CIS subcell. [ 147 ]…”
Section: Other Perovskite‐based Tandem Solar Cellsmentioning
confidence: 99%